Exposed and Sequestered Antigens in Testes and Their Protection by Regulatory T Cell-Dependent Systemic Tolerance - Harakal, Jessica; Qiao, Hui; Wheeler, Karen; Rival, Claudia; Paul, Alberta G. A.; Hardy, Daniel M.; Cheng, C. Yan; Goldberg, Erwin; Tung, Kenneth S. K. (Frontiers in Immunology, 2022)
Continuous exposure of tissue antigen (Ag) to autoantigen-specific regulatory T cells (Treg) is necessary to maintain Treg-dependent systemic tolerance. Thus, testis autoantigens, previously considered as sequestered, may not be protected by systemic tolerance. We now document that the haploid sperm Ag lactate dehydrogenase 3 (LDH3) is continuously exposed and not sequestered. It enters the residual body (RB) to egress from the seminiferous tubules and interact with circulating antibody (Ab), or remains inside the sperm cytoplasmic droplets (CD). Treg-depleted DEREG mice expressing diphtheria toxin receptor on the Foxp3 promoter develop spontaneous experimental autoimmune orchitis (EAO) and Ab to LDH3. Unlike wild-type female mice, mice deficient in LDH3 (wild=type male or LDH3 NULL females) respond vigorously to LDH3. In contrast, zonadhesin (ZAN) in the sperm acrosome displays properties of a sequestered Ag. However, when ZAN and other sperm Ag are exposed by vasectomy, they rapidly induce testis Ag-specific tolerance, which is terminated by 60% Treg-depletion, leading to bilateral EAO and ZAN Ab response. In our new studies, we show that: 1) the distinctions between LDH3 and ZAN are applicable to other Ag localized in the CD and the acrosome respectively; 2) amongst 40 published cognate Ag documented in rodent EAO and infertile men with or without AIRE-deficiency, 75% are located in the murine CD and the RB proteomes; and 3) Treg-depleted DEREG mice spontaneously develop Ab to the Leydig cell enzymes Cyp11a1 and 17α-hydroxylase. We conclude that some testis/sperm Ag are normally exposed because of the unique testicular anatomy and physiology. The exposed Ag: 1) maintain normal Treg-dependent systemic tolerance, and 2) are pathogenic in autoimmune state. Unexpectedly, the sequestered Ag, normally non-tolerogenic, can orchestrate de novo Treg-dependent tolerance when exposed in vasectomy.